Genetic Mapping of the Leaf Number above the Primary Ear and Its Relationship with Plant Height and Flowering Time in Maize - Cui, Min; Jia, Bo; Liu, Huanhuan; Kan, Xin; Zhang, Yu; Zhou, Ronghua; Li, Zhipeng; Yang, Liang; Deng, Dexiang; Yin, Zhitong (Frontiers in Plant Science, 2017)
Abstract: The leaf number above the primary ear (LA) is a major contributing factor to plant architecture in maize. The yield of leafy maize, which has extra LA compared to normal maize, is higher than normal maize in some regions. One major concern is that increasing LA may be accompanied by increased plant height and/or flowering time. Using an F2:3 population comprising 192 families derived from a leafy maize line and a normal maize line, an association population comprising 437 inbred maize lines, and a pair of near-isogenic maize lines, we mapped the quantitative trait loci (QTL) associated with LA and assessed its genetic relationship with flowering time and plant height. Ten QTL with an additive and dominant effect, eighteen pairs of interacting QTL in the F2:3 population and seventeen significant SNPs in the association population were detected for LA. Two major QTL, qLA3-4 and qLA7-1, were repeatedly detected and explained a large proportion of the phenotypic variation. The qLA3-4 was centered on lfy1, which is a dominant gene underlying extra leaves above the ear in leafy maize. Four LA QTL were found to overlap with flowering time and/or plant height, which suggested that these QTL might have a pleiotropic effect. The pleiotropy of the lfy1 locus on LA, flowering time and plant height were validated by near-isogenic line analysis. These results enhance our understanding of the genetic architecture affecting maize LA and the development of maize hybrids with increased LA.